Prosedur Keselamatan Dan Kesehatan Kerja (K3) Pada PT. Satunol Mikrosistem Jakarta - Herry Syafrial; Ahmad Ardiansyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The purpose of this writing is to find out how the K3 procedure in Jakarta's Satunol Mikrosistem and the obstacles faced in the K3 procedure and what solutions can be done to deal with these obstacles.The research method that the author is doing is to look for references from books related to the title that the author took, then by interviewing methods, as well as direct observation to PT Satunol Microsystems.The results of this study, the authors conclude that the K3 procedure at PT Satunol Mikrosistem has been running well and has been in accordance with the rules and provisions of the applicable laws in Indonesia. The purpose of this writing is to find out how the K3 procedure in Jakarta's Satunol Mikrosistem and the obstacles faced in the K3 procedure and what solutions can be done to deal with these obstacles.The research method that the author is doing is to look for references from books related to the title that the author took, then by interviewing methods, as well as direct observation to PT Satunol Microsystems.The results of this study, the authors conclude that the K3 procedure at PT Satunol Mikrosistem has been running well and has been in accordance with the rules and provisions of the applicable laws in Indonesia.